Invent your own computer games - D'Ignazio, Fred. 4 0 16; 5 (New York : F. Watts, 1983)
Explains how to use a personal computer to create original sports, board, strategy, word, number, and adventure games, with instructions for programming and playing eleven simple computer games.
Includes index.
Bibliography: pages 86-87.
School Library Journal;Booklist;Reference and Research Book News
6.3;5-8;5-8
Keywords: 2 -- 0; 6; Programming. -- Computer games.;Games.;BASIC (Computer program language);Programming (Computers);Minicomputers;Computer games.;Basic (Computer program language);Computer programming; 20; 2